Penurunan Kadar Lignin pada Fermentasi Limbah Kayu Mahoni Menggunakan Phanerochaete chrysosporium - Sri Rulianah; Prayitno; Christyfani Sindhuwati; Dessi Ria Ambar Ayu; Khalimatus Sa’diyah (Jurnal Teknik Kimia dan Lingkungan, 2020)
Mahogany wood waste is a type of hard wood agricultural waste containing lignocellulose which is quite high. In mahogany wood waste also contains lignin which is quite high, so the level of lignin must be reduced so that the cellulose can be used as glucose. Phanerochaete chrysosporium is a type of mold that is able to degrade lignin, cellulose and hemicellulose simultaneously. The purpose of this study was to determine the effect of fermentation time and the addition of mahogany wood waste to the reduction of lignin content in the fermentation of mahogany wood waste using Phanerochaete chrysosporium molds. The study was conducted by drying and reducing the size of mahogany wood waste, then fermentation of mahogany wood waste with Phanerochaete chrysosporium with a span of 9, 11, 13, 15, and 17 days, and the addition of mahogany wood waste 5, 6 and 7%. Before and after the fermentation process, lignin levels were analyzed. The best results from this study were obtained at 17 days of fermentation and the addition of 5% mahogany wood powder, obtained a decrease in lignin content of 85,33 %.